2017
DOI: 10.2217/pme-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Mirna-146A Contributes to the Development of Lupus Nephritis Via Targeting of TRAF6

Abstract: Rs2910164 is associated with the risk of LN and could function as a therapeutic target of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
2
Order By: Relevance
“…Contradictory, Alemán-Ávila et al showed significant variations in genotypes distribution of rs2910164 SNP between Mexican SLE patients and controls [ 4 ]. Ambivalent to the current study, Wu et al observed that Chinese patients with lupus nephritis [LN] increased the frequency of the C allele against patients without nephritis [ 43 ]. Also, they documented that the C allele and genotype carriers were associated with LN risk while the G allele worked as a protective factor against increasing the disease complication [ 43 ].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Contradictory, Alemán-Ávila et al showed significant variations in genotypes distribution of rs2910164 SNP between Mexican SLE patients and controls [ 4 ]. Ambivalent to the current study, Wu et al observed that Chinese patients with lupus nephritis [LN] increased the frequency of the C allele against patients without nephritis [ 43 ]. Also, they documented that the C allele and genotype carriers were associated with LN risk while the G allele worked as a protective factor against increasing the disease complication [ 43 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Ambivalent to the current study, Wu et al observed that Chinese patients with lupus nephritis [LN] increased the frequency of the C allele against patients without nephritis [ 43 ]. Also, they documented that the C allele and genotype carriers were associated with LN risk while the G allele worked as a protective factor against increasing the disease complication [ 43 ]. Inconsistent with our study, Labib et al [ 28 ] found significant differences in alleles and genotypes of rs2910164 SNP between Egyptian SLE patients and controls.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…[23][24][25][26] Interestingly, in vitro studies have shown that miR-146a may regulate the IL-1 receptor associated kinase 1 (IRAK-1) and TRAF6 on TLR-4 signaling pathway through negative feedback and may suppress NF-kB activity so as to further reduce the expression of proinflammatory factors, such as TNF-a, IL-6, and IL-1b, [23][24][25] thereby inhibiting the activation of small keratinocytes and reducing the pathological damage caused by their activation. 27 Prior report has highlighted that induction of human miR-146a (has-miR-146a) regulates innate immune response by the mean of targeting TRAF6 and IRAK-1 genes 9. 24 Notably, the sequences of miR-146a, TRAF6, and IRAK-1 exhibit a high degree of nucleotide identity.…”
Section: Discussionmentioning
confidence: 99%